2018
DOI: 10.1002/qj.3316
|View full text |Cite
|
Sign up to set email alerts
|

Large‐eddy simulation of a warm‐air advection episode in the summer Arctic

Abstract: While there is an increasing scientific interest in the role of advection of warm and moist air into the Arctic, there is little understanding of the interactive processes between the advected air, boundary‐layer clouds and turbulence during such events and almost all studies refer to winter conditions. We use large‐eddy simulation (LES) to investigate these processes for an extreme warm‐air advection episode observed during summer 2014. The results indicate that moisture advection is the critical factor for c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
26
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
1
1
1

Relationship

3
5

Authors

Journals

citations
Cited by 17 publications
(27 citation statements)
references
References 43 publications
1
26
0
Order By: Relevance
“…e.g., Pithan et al 2018). Numerical modeling on different scales constitute one way forward, for example single-column or largeeddy modeling at different locations using advection tendencies from reanalysis (e.g., Sotiropoulou et al 2018;Hartung et al 2018), or Lagrangian modeling where a hypothetical atmospheric column is advected along a trajectory over the observed surface conditions (Sotiropoulou 2016;Pithan et al 2014). Modeling needs to be informed by observations, and observation design may also need to consider a Lagrangian framework, as was pioneered in ASTEX (Albrecht et al 1995) but rarely repeated.…”
Section: Discussionmentioning
confidence: 99%
“…e.g., Pithan et al 2018). Numerical modeling on different scales constitute one way forward, for example single-column or largeeddy modeling at different locations using advection tendencies from reanalysis (e.g., Sotiropoulou et al 2018;Hartung et al 2018), or Lagrangian modeling where a hypothetical atmospheric column is advected along a trajectory over the observed surface conditions (Sotiropoulou 2016;Pithan et al 2014). Modeling needs to be informed by observations, and observation design may also need to consider a Lagrangian framework, as was pioneered in ASTEX (Albrecht et al 1995) but rarely repeated.…”
Section: Discussionmentioning
confidence: 99%
“…Spaceborne measurements over this area indicated a rapid decrease in sea ice concentration, from >90% to ~50%, during the examined event (Figures a and b), while the analysis of the surface energy budget revealed a surplus of 30–40 W/m 2 at maximum (Tjernström et al, ). Later, Sotiropoulou et al () showed that this additional energy flux can be attributed entirely to the clouds, maintained by the advected moisture. The key role of moisture and clouds during warm‐air advection episodes has been documented in previous studies as well (e.g., Kapsch et al, ; Park et al, ), albeit these focused on different seasons.…”
Section: Introductionmentioning
confidence: 99%
“…As illustrated in Figure b, the subsidence profile is linearized between the thermal inversion z i and the surface. This corresponds to assuming a constant large‐scale divergence within that height range, a configuration often applied in LES of low cloud transitions (e.g., Loewe et al, ; Neggers et al, ; Sandu & Stevens, ; Sotiropoulou et al, ). One of the main reasons for adopting it here is that the linearization effectively removes any fingerprints of the parameterized boundary layer in the ECMWF model, which should be resolved by the LES itself.…”
Section: Methodsmentioning
confidence: 99%
“…Typically, LES experiments are based on measurements at fixed sites or during field campaigns, with the simulations being critically interpreted and evaluated (Fridlind et al, ; Klein et al, ; Morrison et al, ; Ovchinnikov et al, ). In recent years LES of mixed‐phase clouds in warm air intrusions is increasingly being pursued and is yielding valuable new insights (Loewe et al, ; Savre & Ekman, ; Savre et al, ; Sotiropoulou et al, ).…”
Section: Introductionmentioning
confidence: 99%